High-triplet-level phthalimide based acceptors for exciplexes with multicolor emission. (March 2019) - Chapran, Marian; Lytvyn, Roman; Begel, Corentin; Wiosna-Salyga, Gabriela; Ulanski, Jacek; Vasylieva, Marharyta; Volyniuk, Dmytro; Data, Przemyslaw; Grazulevicius, Juozas Vidas
Abstract: To provide high exciton utilization in organic light emitting diodes, phthalimide derivatives were designed and synthesized as exciplex-forming materials. Due to high triplet levels (2.92–3.11 eV) and ionization potentials (7.18–7.29 eV), the developed phthalimide derivatives were found to be not only appropriate accepting materials for the formation of different color exciplexes but also as bifunctional materials with a satisfactory hole and exciton-blocking abilities. Solid-state blends of the synthesized phthalimides as acceptors and a carbazole containing donors showed exciplex emission. Bimolecular blends exhibited multicolor exciplex emission which covered a visible spectrum from sky-blue to red colors, depending on the donor used. However, the photoluminescence quantum efficiencies of the studied exciplex-forming systems were found to be sensitive to the molecular design of the phthalimides. Acceptor with para-substituted phthalimide showed better exciplex-forming properties in comparison to other compounds. Exciplex-forming blend of (2-(4-benzoylphenyl)isoindoline-1, 3-dione) as an acceptor and 1, 3-di(9H-carbazol-9-yl)benzene (mCP) as a donor showed the most efficient sky-blue emission with small singlet-triplet splitting (0.06 ± 0.03eV). Such exciplex-forming molecular mixture was implemented as the light-emitting material in the sky-blue organic light emitting diodes which showed the brightness of 2500 cd m −2 and maximum external quantum efficiency of 2.9% due to the employment of both singlet and triplet excitons. Graphical abstract: Highlights: Five novel phthalimide based acceptors with high triplet levels (2.92–3.11 eV). Exciplex forming properties of acceptors were sensitive to the molecules design. A para-substituted phthalimide-benzophenone in blend with donor showed sky-blue exciplex emission with ΔEST gap 0.06eV.